2012
DOI: 10.1007/s13280-012-0326-x
|View full text |Cite
|
Sign up to set email alerts
|

How will Ocean Acidification Affect Baltic Sea Ecosystems? An Assessment of Plausible Impacts on Key Functional Groups

Abstract: Increasing partial pressure of atmospheric CO 2 is causing ocean pH to fall-a process known as 'ocean acidification'. Scenario modeling suggests that ocean acidification in the Baltic Sea may cause a B3 times increase in acidity (reduction of 0.2-0.4 pH units) by the year 2100. The responses of most Baltic Sea organisms to ocean acidification are poorly understood. Available data suggest that most species and ecologically important groups in the Baltic Sea food web (phytoplankton, zooplankton, macrozoobenthos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…Considering that the Baltic Sea is a coastal sea with a natural frequent and wide pH variability (Omstedt et al, 2009), it can be expected that the effects of OA on plankton communities will be rather small within the range of predicted values for this century (Havenhand, 2012). A reduced OA sensitivity in systems experiencing high CO 2 fluctuations is supported by our results and other studies using communities from the Baltic (Thomsen et al, 2010;Nielsen et al, 2010;Rossoll et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Considering that the Baltic Sea is a coastal sea with a natural frequent and wide pH variability (Omstedt et al, 2009), it can be expected that the effects of OA on plankton communities will be rather small within the range of predicted values for this century (Havenhand, 2012). A reduced OA sensitivity in systems experiencing high CO 2 fluctuations is supported by our results and other studies using communities from the Baltic (Thomsen et al, 2010;Nielsen et al, 2010;Rossoll et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Annual pH ranges vary from 8. 1-8.4 in the Kattegat area to 7.4-8.4 in the less saline eastern Baltic (Havenhand, 2012). Kiel Fjord and Eckernförde Bay are narrow coastal embayments in the western Baltic Sea.…”
Section: Introductionmentioning
confidence: 98%
“…Salinity may decrease from current 7 to 4, while mid-summer water temperature may increase from 12 to 16°C, and pCO 2 levels may increase from 380 ppm to 960 ppm, by year 2100 (HELCOM 2007). In a recent review concerning the effects of ocean acidification on Baltic ecosystems, it is concluded that it seems likely that the effects on the Baltic spring and summer blooms will be small, and perhaps positive (Havenhand 2012). However, available evidence for Baltic primary producers is scant, and only three relevant studies are referred to.…”
Section: Introductionmentioning
confidence: 99%